Spring peepers Pseudacris crucifer modify their call structure in response to noise. Issue 4 (1st August 2014) - Hanna, Dalal E. L.; Wilson, David R.; Blouin-Demers, Gabriel; Mennill, Daniel J.
Abstract: Acoustic interference can impede effective communication that is important for survival and reproduction of animals. In response to acoustic interference, some animals can improve signalling efficacy by altering the structure of their signals. In this study, we played artificial noise to 46 male spring peepers Pseudacris crucifer, on their breeding grounds, and tested whether the noise affected the duration, call rate, and peak frequency of their advertisement calls. We used two experimental noise treatments that masked either the high- or low-frequency components of an average advertisement call; this allowed us to evaluate whether frogs adaptively shift the peak frequency of their calls away from both types of interference. Our playback treatments caused spring peepers to produce shorter calls, and the high-frequency noise treatment caused them to lower the frequency of their calls immediately after the noise ceased. Call rate did not change in response to playback. Consistent with previous studies, ambient temperature was inversely related to call duration and positively related to call rate. We conclude that noise affects the structure of spring peeper advertisement calls, and that spring peepers therefore have a mechanism for altering signal structure in response to noise. Future studies should test if other types of noise, such as biotic or anthropogenic noise, have similar effects on call structure, and if the observed changes to call structure enhance or impair communication in noisy environments [ Current Zoology 60 (4): 438–448, 2014].